Effects of Atorvastatin (80mg) Therapy on Quantity of Epicardial Adipose Tissue in Patients Undergoing Pulmonary Vein Isolation for Atrial Fibrillation - Soucek, Filip (Am J Cardiol, 2015)
Epicardial adipose tissue (EAT) has been recognized as a sensitive marker of cardiometabolic risk. Recent evidence suggests efficacy of long-term statin therapy in reducing EAT in patients with coronary artery disease. Whether short-term statin therapy is associated with changes in the volume of EAT is currently unknown. A cohort of atrial fibrillation (AF) patients undergoing pulmonary vein isolation was randomized to receive either 80 mg/day of atorvastatin (n=38, 32 males, age 56 ± 11 years) or placebo (n=41, 33 males, age 56 ± 10 years) for a 3-month period. EAT volume was assessed by cardiac computed tomography at baseline and at follow-up. Patients randomized to statin treatment exhibited a modest but significant decrease in median EAT volume (baseline vs follow-up: 92.3(62.0–133.3) vs 86.9(64.1–124.8) cm(3), p < 0.05) while median EAT remained unchanged in the placebo group (81.9(55.5–110.9) vs 81.3(57.1–110.5) cm(3), p = NS). Changes in median systemic inflammatory markers and lipid profile were also seen with statin treatment: C-reactive protein (2.4(0.7–3.7) vs 1.1(0.5–2.7) mg/L, p < 0.05), total cholesterol (186(162.5–201) vs 123(99–162.5) mg/dL, p < 0.001), and low density lipoprotein-cholesterol (116(96.5–132.5) vs 56(40.5–81) mg/dL, p < 0.001) diminished, while median body mass index did not change (27.8(25–30) vs 27.6(25.7–30.5) kg/m(2), p = NS). No variations occurred in the placebo group. In conclusion, short-term intensive statin therapy significantly reduced the volume of EAT in AF patients.